2006
DOI: 10.1158/1078-0432.ccr-06-0800
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Analysis of the Putative Tumor Suppressor km23 in Primary Ovarian, Breast, and Colorectal Cancers

Abstract: Purpose: A very high frequency of somatic mutations in the transforming growth factor-h signaling component km23 has been reported in a small series of ovarian cancers (8 of 19, 42%). Functional studies showed that some mutations disrupt km23 function, resulting in aberrant transforming growth factor-h signaling and presumably enhanced tumorigenicity. If verified, this would elevate mutation of km23 as the single most frequent somatic event in ovarian cancer. Experimental Design: We sought to verify the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Hence we believe that contamination is not an issue. Somatic hypermethylation events have been reported for km23 (a TGF-β receptor-interacting protein), ATM, BRCA1 & 2 [48][49][50]. Our observations on the existence of somatic hypermethylation of BRMS1 may have a bearing on the susceptibility to develop breast cancer metastases or overall patient prognosis; however this study is underpowered to address this issue.…”
Section: Discussionmentioning
confidence: 81%
“…Hence we believe that contamination is not an issue. Somatic hypermethylation events have been reported for km23 (a TGF-β receptor-interacting protein), ATM, BRCA1 & 2 [48][49][50]. Our observations on the existence of somatic hypermethylation of BRMS1 may have a bearing on the susceptibility to develop breast cancer metastases or overall patient prognosis; however this study is underpowered to address this issue.…”
Section: Discussionmentioning
confidence: 81%
“…However, in approximately 30–40% of colon cancers, the mechanism(s) resulting in impaired TGF-β signaling is not known. Some investigators have shown that epigenetic alterations can affect KM23, TGFBI (Betaig-h3 gene), and RUNX3 , which are all genes involved with regulation of the TGF-β signaling pathway, but none of these studies have demonstrated that the aberrant methylation of these genes directly alters the TGF-β signaling pathway 4042. We have provided evidence that TGF-β1 activation is impaired when TSP1 is aberrantly methylated resulting in the suppression of TGF-β receptor activation.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have shown that epigenetic alterations can affect KM23, TGFBI (Betaig-h3 gene), and RUNX3, which are all genes involved with regulation of the TGF-b signaling pathway, but none of these studies have demonstrated that the aberrant methylation of these genes directly alters the TGF-b signaling pathway. [40][41][42] We have provided evidence that TGF-b1 activation is impaired when TSP1 is aberrantly methylated resulting in the suppression of TGF-b receptor activation. These results provide the first evidence of which we are aware that an epigenetic event can attenuate TGF-b responsiveness in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…km23-1, also termed km23 (Campbell et al, 2006; Kang et al, 2007; Tang et al, 2002), Robl1 (Nikulina et al, 2004), DNLC2A (Jiang et al, 2001), mLC7-1 (Tang et al, 2002), DYNLRB1, (Pfister et al, 2005) has been shown to interact with Rab6 (Wanschers et al, 2008), the human reduced folate carrier (Ashokkumar et al, 2009), dynein intermediate chain (DIC) (Susalka et al, 2002; Tang et al, 2002), and LIN-5 and GPR-1/2 in C. elegans (Couwenbergs et al, 2007). We have shown that km23-1 undergoes rapid phosphorylation on serine residues after TßR activation, in keeping with the kinase specificity of the TßRs (Tang et al, 2002).…”
Section: Introductionmentioning
confidence: 99%